Agglutinating activity and structural characterization of Scalarin, the major egg protein of the snail Pomacea scalaris (d'Orbigny, 1832) - Ituarte, Santiago (2012)
Apple snail perivitellins are emerging as ecologically important reproductive proteins. To elucidate if the protective functions of the egg proteins of Pomacea canaliculata (Caenogastropoda, Ampullariidae), involved in embryo defenses, are present in other Pomacea species we studied scalarin (PsSC), the major perivitellin of Pomacea scalaris. Using small angle X-ray scattering, fluorescence and absorption spectroscopy and biochemical methods, we analyzed PsSC structural stability, agglutinating activity, sugar specificity and protease resistance. PsSC aggluttinated rabbit, and, to a lesser extent, human B and A erythrocytes independently of divalent metals Ca2+ and Mg2+ were strongly inhibited by galactosamine and glucosamine. The protein was structurally stable between pH 2.0 to 10.0, though agglutination occurred only between pH 4.0 to 8.0 (maximum activity at pH 7.0). The agglutinating activity was conserved up to 60°C and completely lost above 80°C, in agreement with the structural thermal stability of the protein (up to 60°C). PsSC was able to withstand in vitro gastrointestinal digestion, and showed no trypsin inhibition activity. The presence of lectin activity has been reported in eggs of other Pomacea snails, but here we link for the first time, this activity to an apple snail multifunctional perivitellin. This novel role for a snail egg storage protein is different from closely related P.canaliculata defensive proteins.